2021
DOI: 10.3390/v13091827
|View full text |Cite
|
Sign up to set email alerts
|

The Isolated in Utero Environment Is Conducive to the Emergence of RNA and DNA Virus Variants

Abstract: The host’s immune status may affect virus evolution. Little is known about how developing fetal and placental immune milieus affect virus heterogeneity. This knowledge will help us better understand intra-host virus evolution and how new virus variants emerge. The goal of our study was to find out whether the isolated in utero environment—an environment with specialized placental immunity and developing fetal immunity—supports the emergence of RNA and DNA virus variants. We used well-established porcine models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Pregnant pigs were randomly assigned into Control, E+102CpG, E/NS1+176CpG and WT groups. Results from the pig exposed to the only wild-type virus were partially reported in our previous study (22). All animals were housed in identical isolated rooms at VIDO.…”
Section: Animal Experimentsmentioning
confidence: 73%
See 1 more Smart Citation
“…Pregnant pigs were randomly assigned into Control, E+102CpG, E/NS1+176CpG and WT groups. Results from the pig exposed to the only wild-type virus were partially reported in our previous study (22). All animals were housed in identical isolated rooms at VIDO.…”
Section: Animal Experimentsmentioning
confidence: 73%
“…In addition, the genomic regions amplified with primers that contained nucleotide mismatches within the binding sites were omitted. The detailed computational protocol used in this paper for iVar was previously published ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Eight female Landrace-cross pigs were purchased from the university high-health status herd free from porcine reproductive and respiratory virus (PRRSV), porcine parvovirus (PPV), congenital porcine circovirus 2 (PCV2), and porcine circovirus 3 (PCV3), which can cause fetal infection in pigs. Accordingly, maternal and fetal samples were negative for PRRSV, PPV, PCV2, and PCV3 in virus-specific PCR assays [35,43]. Before delivering to containment, six pigs were synchronized and bred with semen from a single donor to reduce biological variability; two pigs (G and H) remained non-pregnant.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Another study showed that ZIKV diversity in infected mice varied by organs and inoculation routes; however only non-pregnant animals were used, so again fetal tissues were not evaluated [ 14 ]. A recent study evaluated ZIKV diversity in a pregnant pig via in utero inoculation of individual conceptuses and identified some tissue-specific variants as well as a low level of convergent evolution [ 15 ]. Unfortunately, in that study, none of the fetal brains were positive for ZIKV at the study endpoint so variants involved in neuroinvasion could not be evaluated [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study evaluated ZIKV diversity in a pregnant pig via in utero inoculation of individual conceptuses and identified some tissue-specific variants as well as a low level of convergent evolution [ 15 ]. Unfortunately, in that study, none of the fetal brains were positive for ZIKV at the study endpoint so variants involved in neuroinvasion could not be evaluated [ 15 ]. To our knowledge, no study thus far has evaluated whole genome ZIKV diversity within animals during early and late stages of vertical transmission and fetal neuroinvasion.…”
Section: Introductionmentioning
confidence: 99%